ANALISIS STRATEGI PUBLIC RELATIONS DALAM MEMPERBAIKI CITRA PERUSAHAAN (Studi Kasus PT. Pelabuhan Indonesia II Pasca Penetapan Direkur Utama Sebagai Tersangka Korupsi) - Neisya Hanifah, (2020)
A case that happened on a company may have any negative impact on the company, for instance one of the example is the company's image downturn like the one happened on PT. Pelabuhan Indonesia II in which the president director was set as the suspect on a corruption happened in 2015. The case is still making negative impact on the company even untill now. That being said, the purpose of this research is to find out the strategy by the public relations of PT. Pelabuhan Indonesia II on the post-case of the settlement as suspect of the president director. This research is conducted in qualitative approach with interviews as the data collecting method. The theory used in this research is the theory of image restoration. The result shows that public relations of PT. Pelabuhan Indonesia II have done several strategies to increase the company's image such as publication, news update, lobbying, and negotiation. In the other hand, public relations of PT. Pelabuhan Indonesia II also executed assault reduction and corrective act strategy.